Advancements in graft-versus-host disease prevention in hematopoietic stem cell transplantation - Soumyajit Das; Mahendra Pratap Singh; Ashok Kumar Balaraman; Rachana Mehta; Sanjit Sah (Iraqi Journal of Hematology)
Graft-versus-host disease (GVHD) remains a critical obstacle in the success of allogeneic hematopoietic stem cell transplantation (HSCT), adversely affecting patient survival and posttransplant quality of life. Recent advancements in GVHD prophylaxis emphasize achieving a delicate equilibrium between effective immunosuppression and preservation of the graft-versus-tumor (GVT) effect. This article synthesizes cutting-edge developments, including immune modulation strategies such as regulatory T-cell expansion and cytokine blockade, novel pharmacological approaches like Janus kinase inhibitors and posttransplant cyclophosphamide, and cellular therapies leveraging mesenchymal stromal cells and ex vivo-expanded regulatory T cells. Furthermore, the advent of biomarkers such as ST2 and microRNA signatures has enabled early risk stratification, fostering personalized, risk-adapted prophylactic strategies. By integrating these innovations, HSCT outcomes can be significantly improved, offering enhanced safety, reduced GVHD incidence, and optimized long-term patient care.